Idiopathic thrombocytopenic purpura (ITP) - new era for an old disease - Onisâi Minodora; Vlădăreanu Ana-Maria; Spînu Andreea; Găman Mihaela; Bumbea Horia (Sciendo, 2019)
Immune thrombocytopenia is an autoimmune hematological disorder characterized by severely decreased platelet count of peripheral cause: platelet destruction via antiplatelet antibodies which may also affect marrow megakaryocytes. Patients may present in critical situations, with cutaneous and/or mucous bleeding and possibly life-threatening organ hemorrhages (cerebral, digestive, etc.) Therefore, rapid diagnosis and therapeutic intervention are mandatory.